Impact of a Health Empowerment-focused Program on Adult Employee's Motivators of and Barriers to Engaging in Healthy Behaviors. Issue 3 (3rd May 2020) - Williams, Jaime; Tucker, Carolyn M.; Wippold, Guillermo; Roncoroni, Julia; Moutinho, Maria E.; Lee, Susan; Desmond, Frederic; Ateyah, Wafaa
ABSTRACT: Background : Health initiatives have been established in many workplaces to promote healthy behaviors among employees. Health Self-Empowerment Theory (HSET) suggests that personal, modifiable factors, such as motivation to engage in healthy behaviors, are pathways to increasing such behaviors. Purpose : The present study examined the effects of the Health-Smart Behavior Program TM (Health-Smart), which is informed by HSET, on levels of perceived motivators of and barriers to engaging in healthy eating and physical activity among a sample of employees at a large health insurance company. Methods : Participants were 97 culturally diverse employees at this company who were divided into intervention and control groups. Results : From pre-intervention to post-intervention, the intervention group experienced significantly greater increases in motivators to engage in healthy eating and physical activity and significantly greater decreases in barriers to engaging in these behaviors. Discussion : Health-Smart may be effective in increasing motivation to engage in healthy behaviors among workplace employees. Translation to Health Education Practice : This study suggests that health educators who develop workplace health promotion programs use a theoretical framework (e.g., HSET) to inform these programs, implement a first-step program to increase motivators of and reduce barriers to these behaviors, and empirically evaluate these programs.